Habitat selection can reduce effects of extreme climatic events in a long‐lived shorebird. Issue 10 (27th June 2019) - Bailey, Liam D.; Ens, Bruno J.; Both, Christiaan; Heg, Dik; Oosterbeek, Kees; van de Pol, Martijn
Abstract: Changes in the frequency of extreme climatic events (ECEs) can have profound impacts on individual fitness by degrading habitat quality. Organisms may respond to such changes through habitat selection, favouring those areas less affected by ECEs; however, documenting habitat selection in response to ECEs is difficult in the wild due to the rarity of such events and the long‐term biological data required. Sea level rise and changing weather patterns over the past decades have led to an increase in the frequency of coastal flooding events, with serious consequences for ground nesting shorebirds. Shorebirds therefore present a useful natural study system to understand habitat selection as a response to ECEs. We used a 32‐year study of the Eurasian oystercatcher ( Haematopus ostralegus ) to investigate whether habitat selection can lead to an increase in nest elevation and minimize the impacts of coastal flooding. The mean nest elevation of H. ostralegus has increased during the last three decades. We hypothesized that this change has been driven by changes in H. ostralegus territory settlement patterns over time. We compared various possible habitat selection cues to understand what information H. ostralegus might use to inform territory settlement. There was a clear relationship between elevation and territory settlement in H. ostralegus . In early years, settlements were more likely at low elevations but in more recent years the likelihood of settlement was similar between high and low elevation areas. Territory settlement was associated with conspecific fledgling output and conspecific density. Settlement was more likely in areas of high density and areas with high fledgling output. This study shows that habitat selection can minimize the effects of increasingly frequent ECEs. However, it seems unlikely that the changes we observe will fully alleviate the consequences of anthropogenic climate change. Rates of nest elevation increase were insufficient to track current increases in maximum high tide (0.5 vs. 0.8 cm/year). Furthermore, habitat selection cues that rely on information from previous breeding seasons (e.g. conspecific fledgling output) may become ineffective as ECEs become more frequent and environmental predictability is diminished. Abstract : The authors use 30 years of coastal shorebird breeding data to demonstrate how habitat selection can reduce the effects of more frequent extreme climatic events. Changes in the territory settlement behaviour of birds have led to an increase in nest elevation. Higher elevation nest sites are less affected by flooding events.